Additives in growing-finishing rations - Koch, B.A.; Loeppke, D.W. (Kansas Agricultural Experiment Station, 2011)
Specific additives are successfully incorporated into swine rations. Each year new ones are approved and each year the efficacy of the older ones is questioned. Recent feeding trial comparisons at this station are summarized here. Pigs used were both barrows and gilts. They included Durocs, Poland Chinas, and crossbreds. Each weighed nearly 100 pounds going on tests. Prior to the test the pigs had been together on brome-alfalfa pasture.
Keywords: Swine; Additives; Performance data; Feed efficiency